Obama’s foreign policy legacy: American assessments - Varivonchik, Ivan V. (Journal of the Belarusian State University. International Relations, 2018)
Political discourse in the US is characterized by deep disagreements in assessing the outcome of Obama’s foreign policy. The incumbent President keeps on trying to revise its results. The article is an overview of the most frequently used arguments made by the main political opponents – the Republicans and the Democrats, by those who had been working for the last two administrations and by the leading experts, who were directly involved in the elaboration and implementation of the American foreign policy. Their arguments and views shape the public opinion and constitute the ideological basis for the active politicians. The content of the article demonstrates that, despite the unity in determining the objectives of foreign policy, there is a sharp divide in assessing the results that have been achieved, in choosing methods of achieving goals, and the views on the strategy and tactics of ensuring national interests are diametrically opposed. The polarization of the ruling circles seriously complicates the activities of the ruling administration. D. Trump’s electoral promises on foreign policy could hardly be fulfilled without its substantial modification.